Struktur Kepemilikan dan Model Manajemen Laba Short Term Discretionary Accrual Perusahaan Go Public di Indonesia - Wiyadi, W; Fauziah, Nur Ismiyati; Trisnawati, Rina (Prosiding University Research Colloquium, 2018)
Asymmetry information between agent and principal provides an opportunity for managers to act opportunistically by doing earnings management. Companies need to implement good corporate governance mechanisms in the company's control and management system to minimize earnings management action. This study aims to analyze the effect of ownership structure on earnings management on go public companies in Indonesia with approach short term discretionary accrual model period 2011-2015. The ownership structure used includes concentration of ownership, institutional ownership, foreign ownership, and family ownership. The short term discretionary accrual model used to measure earnings management. The sampling technique was done by purposive sampling, total of sample are 245 samples which have fulfilled classical assumption and analyzed by multiple regression analysis. The results provide empirical evidence that the ownership structure as measured by the concentration of ownership has a significant negative effect on earnings management on go public companies in Indonesia. While institutional ownership, foreign ownership, and family ownership have no effect on earnings management on go public company in Indonesia.